Pemahaman Guru Terhadap Standar Isi Sekolah Lanjutan Tingkat Pertama Kota Bandung - Umniyatul Azizah; Chairul Rahman; Ida Farida; Nina Nurmilasari (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2021)
This study aims to explain a comparative analysis of the content standards among 5 PAI teachers (Teacher of Islamic Education) and 5 Non PAI teachers (Not the Teacher of Islamic Education), and to find out the legal basis for the content standards and then note on each indicator appears. The method used in this research is the descriptive quantitative method. The population of this research is Junior (Islamic) High School (SMP/MTS) in Bandung. The data collection techniques applied in this research are observation, questionnaire, documentation, and data analysis. Retrieval of data and observation which used is google form that was distributed to 5 PAI teachers and 5 Non-IRE (Islamic Religious Education) teachers. The result of collecting authentic data and data triangulation through interviews with teachers and through comparative data analysis between IRE and Non-IRE shows that from 5 points presented by the researcher, PAI is superior in 3 points, while Non-IRE is superior in 2 points.